ETMR stem-like state and chemo-resistance are supported by perivascular cells at single-cell resolution - Faria, Flavia W. de; Riedel, Nicole C.; Münter, Daniel; Interlandi, Marta; Göbel, Carolin; Altendorf, Lea; Richter, Mathis; Melcher, Viktoria; Thomas, Christian; Roy, Rajanya; Schoof, Melanie; Bedzhov, Ivan; et al. (Nature Communications, 2025)
Embryonal tumor with multilayered rosettes (ETMR) is a lethal embryonal brain tumor entity. To investigate the intratumoral heterogeneity and cellular communication in the tumor microenvironment (TME), we analyze in this work single-cell RNA sequencing of about 250,000 cells of primary human and murine ETMR, in vitro cultures, and a 3D forebrain organoid model of ETMR, supporting the main findings with immunohistochemistry and spatial transcriptomics of human tumors. We characterize three distinct malignant ETMR subpopulations - RG-like, NProg-like and NB-like - positioned within a putative neurodevelopmental hierarchy. We reveal PDGFRβ+ pericytes as key communication partners in the TME, contributing to stem cell signaling through extracellular matrix-mediated interactions with tumor cells. PDGF signaling is upregulated in chemoresistant RG-like cells in vivo and plays a role in recruiting pericytes to ETMR TME by finalizing a signaling cascade which promotes the differentiation of non-malignant radial glia cells, derived from our 3D model, into pericyte-like cells. Selective PDGFR-inhibition blocked the lineage differentiation into pericytes in vitro and reduced the tumor cell population in vivo. Targeting ETMR-pericyte interactions in the TME presents a promising therapeutic approach.